Influences of tropical monsoon and El Niño Southern Oscillations on surface chlorophyll-a variability in the Gulf of Thailand - Leenawarat, Dudsadee; Luang-on, Jutarak; Buranapratheprat, Anukul; Ishizaka, Joji (Frontiers in Climate, 2022)
This study investigated the seasonal variability of surface chlorophyll-a (chl-a) and the influence of the El Niño Southern Oscillation (ENSO) related to environmental parameters in the Gulf of Thailand (GoT). Monthly chl-a data from MODIS from 2002 to 2020 as well as sea surface temperature (SST), wind, precipitation, and river discharge were used in this analysis. Results from seasonal climatology and Empirical Orthogonal Function (EOF) described high chl-a concentration areas along the western to the southern coasts and near Ca Mau Cape during the northeast monsoon (NEM), and the upper GoT (UGoT), eastern coast, and the GoT mouth during the southwest monsoon (SWM), while low chl-a took place during the non-monsoon (NON). The GoT was divided into six areas based on the EOFs of chl-a, and then the correlation between chl-a variability and environmental parameters was also examined. The results suggested that chl-a in coastal and offshore areas were controlled by different mechanisms. Chl-a in coastal areas responded to precipitation and river discharge as well as the shoreward wind; meanwhile, chl-a in offshore areas correlated with SST and wind magnitude indicating the importance of water mixing and upwelling. The fluctuation of chl-a in each season related to ENSO was captured by EOF based on the seasonal anomaly. The influence of ENSO was strong during NEM and NON but minimal during SWM. El Niño/La Niña generally caused low/high precipitation and high/low SST. Moreover, El Niño/La Niña caused anomalously weak/strong wind during NEM contrary to during NON. Anomalous high/low chl-a were observed in shallow regions during El Niño/La Niña corresponding to strong/weak wind in NON. Abnormal wind under ENSO also created the shifting in the high chl-a area near cape Ca Mau. These results have improved our understanding of monsoons and ENSO variabilities as the crucial drivers of changes in the tropical marine ecosystem in both seasonal and interannual time scales.